Naples Prognostic Score: A Novel Predictor of Survival in Patients with Triple-Negative Breast Cancer - Qiu Y; Chen Y; Shen H; Yan S; Li J; Wu W (Dove Medical Press, 2024)
Yu Qiu,1,2,* Yan Chen,1,2,* Haoyang Shen,1,2 Shuixin Yan,1,2 Jiadi Li,1,2 Weizhu Wu1 1The Affiliated Lihuili Hospital, Ningbo University, Ningbo, 315000, People's Republic of China; 2Health Science Center, Ningbo University, Ningbo, Zhejiang, 315000, People's Republic of China*These authors contributed equally to this workCorrespondence: Weizhu Wu, The Affiliated Lihuili Hospital, 1111 Jiangnan Road, Ningbo, Zhejiang, 315000, People's Republic of China, Tel +86 574 13957402451, Email wuweizhu1128@163.comPurpose: This study investigated the correlation between the Naples prognostic score (NPS), clinicopathological traits, and the postoperative prognoses of patients with triple-negative breast cancer (TNBC). Based on NPS, a predictive nomogram was developed to estimate the long-term survival probabilities of patients with TNBC post-surgery.Patients and Methods: We retrospectively examined the clinical records of 223 women with TNBC treated at Ningbo Medical Center, Lihuili Hospital between January 1, 2016 and December 31, 2020. Blood tests and biochemical analyses were conducted before surgery. The prognostic nutritional index (PNI), controlling nutritional status (CONUT), neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and NPS were determined based on blood-related markers. A Kaplan-Meier survival analysis assessed the association between NPS, PNI, CONUT score, overall survival (OS), and breast cancer-specific survival (BCSS). Predictive accuracy was evaluated using the area under the receiver operating characteristic curve (AUC) and C index. The patients were randomly divided into the training and the validation group (6:4 ratio). A nomogram prediction model was developed and evaluated using the R Software for Statistical Computing (RMS) package.Results: NPS outperformed other scores in predicting inflammation outcomes. Patients with an elevated NPS had a poorer prognosis (P< 0.001). Lymph node ratio (LNR), surgical method, postoperative chemotherapy, and NPS independently predicted OS, whereas M stage, LNR, and NPS independently predicted BCSS outcome. The OS and BCSS predicted by the nomogram model aligned well with the actual OS and BCSS. The decision curve analysis showed significant clinical utility for the nomogram model.Conclusion: In this study, NPS was an important prognostic indicator for patients with TNBC. The nomogram prognostic model based on NPS outperformed other prognostic scores for predicting patient prognosis. The model demonstrated a clear stratification ability for patient prognosis, which emphasized the potential benefits of early intervention for high-risk patients.Plain Language Summary: In this study, we aimed to understand how the Naples prognostic score (NPS) scoring system could predict the prognosis for patients with triple-negative breast cancer (TNBC). TNBC is a type of breast cancer that can be difficult to treat. Medical records of 223 women with TNBC were retrospectively analyzed. These women had their blood tested before surgery to check for certain markers related to nutrition and inflammation. NPS was used along with other scores to determine their accuracy in predicting survival. NPS was better at predicting outcomes than the other scores. The patients with higher NPS scores tended to have poorer outcomes. We also created a visual tool called a nomogram to help doctors predict patient outcomes based on the NPS scores. NPS can be a valuable tool for doctors treating patients with TNBC because it can help them predict how well a patient might do after surgery. This information could be used to tailor treatment plans for these patients. The nomogram provides a user-friendly way for doctors to use NPS in their practice. Overall, this study showed that NPS is a powerful tool for predicting outcomes for patients with TNBC, which could lead to better treatment decisions and improved outcomes for these patients.Keywords: triple-negative breast cancer, Naples prognostic score, prognostic factor, nomogram predictive model